DESIGNING CULTURALLY INTEGRATED PROJECT-BASED LEARNING TO ENHANCE FINANCIAL LITERACY: A STUDY OF THE JIMPITAN TRADITION IN INDONESIAN ELEMENTARY SCHOOLS - Ita Kurniawati; Fiena Saadatul Ummah; Ari Metalin Ika Puspita (SOSIOEDUKASI, 2025)
Financial literacy is a crucial 21st-century competency that must be developed from an early age to prepare students for real-world financial decision-making. However, learning in many Indonesian elementary schools remains conventional and has not yet integrated meaningful, contextual, and culturally relevant learning experiences. This study aims to design and analyze project-based learning (PjBL) activities integrated with the local Jimpitan tradition to enhance fifth-grade students’ financial literacy at SDN 2 Kloposepuluh, Sukodono District. Using a design-research approach with a qualitative descriptive method, data were collected through observations, interviews, and document analysis involving students, teachers, and school leaders. The learning design guided students to engage in projects related to the Jimpitan practice, including reporting on fundraising processes, management mechanisms, and their financial implications. The findings show that culturally contextualized PjBL activities effectively improved students’ financial literacy, particularly in understanding needs versus wants, money management, and simple economic concepts. Students also demonstrated increased engagement, creativity, and collaboration compared to conventional learning. Challenges such as limited time and resources indicate the need for stronger collaboration between schools, teachers, and researchers. This study contributes to the development of innovative, practical learning models that integrate local cultural wisdom into elementary economics education.